PEMBELAJARAN BAHASA SUNDA DI WILAYAH PERBATASAN: DILEMA IMPLEMENTASI KURIKULUM 2013 - Pramswari, Lungguh Puri (Mimbar Sekolah Dasar, 2014)
Curriculum 2013 provides flexibility to all practitioners of formal education to continue to develop local contentas a form of wealth typical of the region that needs to be maintained and preserved. One of the local content that its existence has importance values is Bahasa Sunda. Teaching Bahasa Sunda in a region where based on a strong Sundanese culture, will not encounter many obstacles. However, in the corners of the area which incidentally is the city/county with very heterogeneous demographi cconditions, of course teaching Bahasa Sunda will be filled with challenges. For example, in areas bordering other culture such Betawi and Java, because of the flexibility of the culture, Sundanese people will be influenced by the Betawior Javanese speech and cultured. This paper is the result of research conducted on the raised border of the city of Bogor, on the implementation of Curriculum 2013, which continued to develop local content Bahasa Sunda to equip students with the knowledge, skills, and attitude typical of Sundanese culture appropriate local wisdom. But on the other hand, collided with a dilemma, where border communitiesis very heterogeneous, so the Sundanese culture and language had not been well maintained. Keywords: local content, Sundanese, cultural borders.